NEST3D printed bone-mimicking scaffolds: assessment of the effect of geometrical design on stiffness and angiogenic potential - Doyle, Stephanie E.; Pannella, Micaela; Onofrillo, Carmine; Bellotti, Chiara; Di Bella, Claudia; O’Connell, Cathal D.; Pirogova, Elena; Lucarelli, Enrico; Duchi, Serena (Frontiers in Cell and Developmental Biology, 2024)
Tissue-engineered implants for bone regeneration require consideration regarding their mineralization and vascularization capacity. Different geometries, such as biomimetic designs and lattices, can influence the mechanical properties and the vascularization capacity of bone-mimicking implants. Negative Embodied Sacrificial Template 3D (NEST3D) printing is a versatile technique across a wide range of materials that enables the production of bone-mimicking scaffolds. In this study, different scaffold motifs (logpile, Voronoi, and trabecular bone) were fabricated via NEST3D printing in polycaprolactone to determine the effect of geometrical design on stiffness (10.44 ± 6.71, 12.61 ± 5.71, and 25.93 ± 4.16 MPa, respectively) and vascularization. The same designs, in a polycaprolactone scaffold only, or when combined with gelatin methacryloyl, were then assessed for their ability to allow the infiltration of blood vessels in a chick chorioallantoic membrane (CAM) assay, a cost-effective and time-efficient in ovo assay to assess vascularization. Our findings showed that gelatin methacrylolyl alone did not allow new chorioallantoic membrane tissue or blood vessels to infiltrate within its structure. However, polycaprolactone on its own or when combined with gelatin methacrylolyl allowed tissue and vessel infiltration in all scaffold designs. The trabecular bone design showed the greatest mineralized matrix production over the three designs tested. This reinforces our hypothesis that both biomaterial choice and scaffold motifs are crucial components for a bone-mimicking scaffold.